2012
DOI: 10.1007/s10404-012-0991-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical breakup of bubbles at a microfluidic T-junction divergence: feedback effect of bubble collision

Abstract: International audienceThis paper aims at studying the asymmetrical breakup of bubbles at a microfluidic T-junction divergence stemming from the feedback effect of bubble behaviors at the T-junction convergence in a loop with the symmetrical branches by a high-speed digital camera. The experiments were performed under gas/liquid flow rates ratio ranging from 0.084 to 4.333. The microfluidic channels have uniform square cross-section with 400 mu m wide and 400 mu m deep. Four bubble behaviors (bubble pair asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Previous studies have shown that a low viscosity ratio between disperse phase and continuous phase and the presence of surfactants are the prerequisites for forming the tip stream (De Bruijn, 1993;Eggleton et al, 2001;Moyle et al, 2012;Stone, 1994). Our previous studies (Wu et al, 2012) and this work have also proved the conclusion. In addition, the experimental results in this work indicate that the tip stream formation is a time-dependent process.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies have shown that a low viscosity ratio between disperse phase and continuous phase and the presence of surfactants are the prerequisites for forming the tip stream (De Bruijn, 1993;Eggleton et al, 2001;Moyle et al, 2012;Stone, 1994). Our previous studies (Wu et al, 2012) and this work have also proved the conclusion. In addition, the experimental results in this work indicate that the tip stream formation is a time-dependent process.…”
Section: Resultssupporting
confidence: 85%
“…Wetting behavior was shown to play a significant role on the formation and motion of the bubbles. Feedback effects of bubble collision on bubble behavior at the convergence and divergence of a T-junction were investigated by Wu et al [23]. Fu et al found that the slug bubble formation process could be divided into expansion, collapsing, and pinch-off.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Shi et al [20] simulated the droplet formation in a two-dimensional symmetric T-junction by using the free-energy lattice Boltzmann method developed by Liu and Zhang [9], and investigated the effect of various parameters on the droplet size, including flow rate ratio, capillary number, geometry, and wetting property. Quite recently, asymmetric T-junctions have emerged as a promising tool for microfluidic functions, e.g., the asymmetric T-junctions have been applied in droplet breakup process to divide one droplet into two unequal parts [21][22][23]. In asymmetric T-junctions, the width of inlet channel of the continuous phase w c1 is unequal to the width of outlet channel w c2 , which provides a new controlling parameter for droplet formation, written as the channel width ratio Z ¼ w c1 =w c2 .…”
Section: Introductionmentioning
confidence: 99%